Tumor-infiltrating lymphocytes in colorectal carcinoma - Karki, Shovana; Pariyar, Sanjib (Journal of Pathology of Nepal, 2021)
Background: Immunotherapy has become an important modality of treatment for CRC. The cells contributing to an effective immune response are CD8+ T cells of tumor-infiltrating lymphocytes. The present study aimed to assess the tumor-infiltrating lymphocytes on colorectal cancer and correlate them with other prognostic parameters. Material and methods: Cases of colectomy from April 2019 -Sept 2020 with a diagnosis of colorectal carcinoma were included in the study. Parameters i.e age, sex, size, location of the tumor, lymphovascular invasion, perineural invasion, T stage, N status, histological tumor type, and grade, resected margins were retrieved from the database of the department. The intensity of overall inflammatory cell reaction at the invasive tumor front was evaluated in H and E stained sections. Results: 56 cases of colorectal cancers were reported during the study period with M: F ratio of 1.15:1. The age ranged from 23-79years with a mean age of 54.3years. The tumors were predominant in the colon (50 cases) than the rectum. Colonic carcinomas had high-grade tumor-infiltrating lymphocytes as compared to rectal carcinomas. The grade of tumor-infiltrating lymphocytes was statistically significantly associated with T, N status, and grade of tumors. Conclusions: Inflammatory reactions at the invasive tumor front can be easily analyzed in resection specimens of colorectal cancers without additional costs. Low-grade tumor-infiltrating lymphocytes are indicative of high-stage tumors with a poor prognosis. Hence, the inclusion of tumor-infiltrating lymphocytes in pathological reports for risk stratification of the patient is mandatory.